2012
DOI: 10.2337/db11-1466
|View full text |Cite
|
Sign up to set email alerts
|

B-Type Natriuretic Peptide Modulates Ghrelin, Hunger, and Satiety in Healthy Men

Abstract: Chronic heart failure is accompanied by anorexia and increased release of B-type natriuretic peptide (BNP) from ventricular cardiomyocytes. The pathophysiological mechanisms linking heart failure and appetite regulation remain unknown. In this study, we investigated the impact of intravenous BNP administration on appetite-regulating hormones and subjective ratings of hunger and satiety in 10 healthy volunteers. Participants received in a randomized, placebo-controlled, crossover, single-blinded study (subject)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 25 publications
2
41
0
Order By: Relevance
“…A study performed in healthy fasting volunteers has shown that BNP infusion decreases hunger and increases satiety, possibly by lowering circulating ghrelin levels (34). Ghrelin also has direct cardiovascular effects (43), and this supports the existence of a bidirectional heart-gut cross talk.…”
Section: Biological Actions Of Nps and Metabolismmentioning
confidence: 94%
“…A study performed in healthy fasting volunteers has shown that BNP infusion decreases hunger and increases satiety, possibly by lowering circulating ghrelin levels (34). Ghrelin also has direct cardiovascular effects (43), and this supports the existence of a bidirectional heart-gut cross talk.…”
Section: Biological Actions Of Nps and Metabolismmentioning
confidence: 94%
“…[55]. These peptides can trigger autoantibodies like IgA and IgG as well as affect the nerve signalling of human and other mammalian animals thus controlling hunger and satiety [56].…”
Section: Functional Metabolites Produced By the Gut Microbiotamentioning
confidence: 99%
“…The BNP hormone is also known to be clinically useful as of ANP and the human recombinant BNP, clinically also known as nesiritide (trade name Natrecor) mimics and has same actions as that of endogenous BNP [148150]. It has been shown to cause a potential decrease in vascular pressure and a reduction in tension in the walls of blood vessels, which are the main hallmarks of vasorelaxation [149].…”
Section: Therapeutic and Clinical Applications Of Natriuretic Peptmentioning
confidence: 99%
“…It has been shown to cause a potential decrease in vascular pressure and a reduction in tension in the walls of blood vessels, which are the main hallmarks of vasorelaxation [149]. Furthermore, natrecor treatment is also accompanied with an increase in natriuresis and diuresis, as well as decrease in plasma aldosterone and endothelin levels in patients with acute heart failure [150]. The intravenous BNP infusion is shown to reduce total and plasma acylated ghrelin concentrations in healthy volunteers [151].…”
Section: Therapeutic and Clinical Applications Of Natriuretic Peptmentioning
confidence: 99%